2019
DOI: 10.3906/tar-1903-56
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depth-dependent irrigation regimes and organomineral fertilizers on water use and quality attributes of sugar beet

Abstract: Experiments were conducted under provincial conditions of Kayseri, Turkey, for two years in the growing seasons of 2014 and 2015 to determine the effects of irrigation water applications based on different sugar beet root zone depths and different organomineral fertilizers on sugar beet yield, root quality, water consumption, and water use efficiency. Two constant root depths (D 1 = 0.9 m and D 2 = 0.6 m) and one active water extraction root depth (D 3 = 0.4-0.9 m) were investigated. A mineral fertilizer (F 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Fertilization plays a crucial role in increasing nutrient availability and plant productivity (Ryan, 2008;Ünlükara, 2019;Aung et al, 2020). However, the improper use of chemical fertilizer can put our natural environments at high risk due to leaching and surface runoff, especially in high-rainfall areas (Castillo, 2010;Stipešević et al, 2019;Nadkarni and Wheelwright, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization plays a crucial role in increasing nutrient availability and plant productivity (Ryan, 2008;Ünlükara, 2019;Aung et al, 2020). However, the improper use of chemical fertilizer can put our natural environments at high risk due to leaching and surface runoff, especially in high-rainfall areas (Castillo, 2010;Stipešević et al, 2019;Nadkarni and Wheelwright, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…small-sized), with tricolporate or tricolpate pollen grains and mostly striate exine ornamentation (Nazeri 2008;Polyakova and Gataulina 2008;Wrońska-Pilarek and Jagodziński 2011;Wrońska-Pilarek et al 2013, 2019Lechowicz et al 2020). Moreover, intra-generic studies indicated that pollen grains were so similar that usually it was possible to distinguish only a few sections or series and from a few to several individual species, and most often there were groups of taxa with similar pollen characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Other genera of the Rosaceae family (e.g. Spiraea, Rosa, and Crataegus) showed a greater correlation between pollen morphology and infrageneric taxonomic classification (Wrońska-Pilarek and Jagodziński 2011;Wrońska-Pilarek et al 2013, 2019. In Rubus this may be the result of apomixes, that is the replacement of the normal sexual reproduction by asexual reproduction, without fertilization, which could reduce natural variability (Weber 1996;Zieliński 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop plants are genetically very diverse groups grown in temperate, subtropical and tropical regions and have been recognized for their human health benefits by containing high contents of non-nutritive, nutritive and bioactive compounds such as flavonoids, phenolics, sugars, essential oils, minerals etc ( Zia-ul-Haq et al., 2014 ; Oktem, 2019 ; Unlukara, 2019 ). Urdbean ( Vigna mungo (L.) Hepper) is an important rainfed short duration legume crop of India and is considered as an excellent source of high-quality dietary protein with good digestibility.…”
Section: Introductionmentioning
confidence: 99%